Multiple complications of the induction phase chemotherapy for childhood acute lymphoblastic leukemia - Dorota Jedlińska; Marcelina Kaleta; Joanna Zawitkowska; Andrzej Kościuk; Monika Lejman; Agnieszka Zaucha-Prażmo; Katarzyna Drabko (Journal of Education, Health and Sport, 2019)
Chemotherapy for childhood acute lymphoblastic leukemia (ALL) despite of high efficiency often leads to many different complications, what bring consequences like therapy failure, death, breaks in chemotherapy, elongate hospitalization. We reported case old 6-year-old girl treated with ALL, who experienced many, severe complications of chemotherapy during the induction phase of treatment.